2020
DOI: 10.31015/jaefs.2020.2.5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of defoliant application on yield and yield components of some cotton (Gossypium hirsutum L.) cultivars at timely and late sowing

Abstract: This study was aimed to assess the effect of defoliant application on yield and yield components of some cotton cultivars at timely and late sowing under Harran Plain conditions in 2017 and 2018 growing seasons. Field trials were arranged employing randomized blocks split-split plots design with 3 replications. In the study, sowing times (i.e.10 th of May and 10 th of June) consisted the main plots, cultivars (i.e. Candia and Lima) placed in the sub-plots and defoliant applications (i.e. Control and Dropp Ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
3
1
0
Order By: Relevance
“…Boll weight is the most important factor that directly contributes to cotton yield (Table 3). Similar to our findings, Qamar et al, (2016) and Haliloğlu et al (2020) indicated that the delay in sowing time causes a decrease in boll weight. Killi et al (2005) reported that boll seed weight decreased by 14% in late sowing.…”
Section: Boll Weight (G)supporting
confidence: 93%
See 2 more Smart Citations
“…Boll weight is the most important factor that directly contributes to cotton yield (Table 3). Similar to our findings, Qamar et al, (2016) and Haliloğlu et al (2020) indicated that the delay in sowing time causes a decrease in boll weight. Killi et al (2005) reported that boll seed weight decreased by 14% in late sowing.…”
Section: Boll Weight (G)supporting
confidence: 93%
“…The fiber yield per plant obtained in normal sowing (128.44 and 126.51 g) was higher in both years of the experiment than the late sowing (73.33 and 83.35 g) (Table 4). The findings on higher fiber yield per plant in normal sowing compared to late sowing are in accordance with the findings of Qamar et al (2016), Hussain et al (2020), Haliloğlu et al (2020), Dhir et al (2021) and Tariq et al (2021). The fiber yield per plant (109.68 and 114.68 g) of the Candia variety was higher in 2017 and 2018 compared to the Lima variety (92.09 and 97.17 g) (Table 5).…”
Section: Fiber Yield Per Plant (G)supporting
confidence: 91%
See 1 more Smart Citation
“…As senescence is progressing, a swelling of thylakoid membranes, a slight increase in the number of plastoglobuli, and a decrease of pigment contents is observed; eventually leading to the degradation of the thylakoid membranes, the significant increase in the number and size of plastoglobuli, and to the further decrease of chlorophyll contents [22]. [23] and [24] indicated that the seed cotton weight decreased by 14% in late sowing results were coinciding with our study. Ethephon (0.5%) and Thidiazuron + Diuron (0.03%) showed higher yield than other treatments.…”
Section: Effect Of Defoliants On Physiological Parameterssupporting
confidence: 90%